ULTRASOUND-ASSISTED EXTRACTION OF SUNFLOWER OIL FROM THE CAKE AFTER PRESSING HULLED SUNFLOWER SEED - Milenković, Dragan D; Milosavljević, Milutin M; Bojić, Aleksandar LJ (Journal of Agricultural Sciences (Belgrade), 2018)
Abstract: The influence of ultrasound application on the extraction (UE) of the cake after the sunflower seeds pressing was in this paper investigated. Three different solvents were used for extraction in the Soxhlet apparatus: n-hexane, petroleumether and extraction petrol. Petrol for extraction, the highest yield showed. It has been shown that the application of ultrasound has a positive effect on the extraction kinetics in the initial period-washing and in the second period in the diffusion of oil from the mass of the cake. The parameters of the non-stationary diffusion model with and without the use of ultrasound were k' = 0.039 min-1, k' = 0.026 min-1 and b' = 0.713 i.e. b' = 0.589, respectively. Oil yield is also slightly higher in ultrasonically supported extraction.
Keywords: ultrasound; extraction; sunflower